A Basic Study on Science Picture Books for Potential Use in Early Childhood Science Education: Focusing on the Relationship with the “Environment” of the Course of Study for Kindergarten - KIMURA, Yuuri (Journal of Science Education in Japan, 2022)
The purpose of this research was to give an overview of Japanese science picture books by focusing on the relationship with the “environment”, as a basis for examining the roles and the potential uses of science picture books in early childhood science education. The subjects of the survey were two kinds of monthly science picture books published in the past 3 years, a total of 72 books. First, based on previous researches, they were analyzed according to the science fields they covered. As a result, it was shown that the proportion of animals and plants was large, as in previous researches. On the other hand, however, more than half of them also dealt with other fields. Then, they were analyzed according to the classification checklist of the science picture books based on the contents of “environment”. The result showed that the following topics were applicable to many science picture books; “5. Interest in their nature and organization”, “8. Interest in things surrounding them, such as nature”, “4. Contact with various things in their lives”, “14. Interest in surrounding things”, “22. Curiosity about the information that play an important role in their lives”, “16. Find a relationship”, and “15. Compare”.